E-cigarette Health Effects on Major Body Systems: A Comprehensive Review of Cardiovascular, Respiratory, and Diabetic Implications - Tomaszewski, Jakub; Borowska-Łygan, Martyna; Rejmak, Rafał Wojciech; Karamus, Kornelia; Biłogras, Jan; Strużek , Konrad; Urban, Wojciech (Journal of Education, Health and Sport, 2025)
This systematic review examined the health implications of electronic cigarette (e-cigarette) use, focusing on cardiovascular, pulmonary, and metabolic effects through analysis of literature published between 2016 and 2023. The study utilized PubMed and Web of Science databases to identify relevant research, including clinical trials and observational studies. Findings indicate that e-cigarette use is associated with both acute and chronic cardiovascular effects, pulmonary and metabolic impacts. The review concludes that e-cigarette use poses significant health risks, particularly for individuals with pre-existing conditions such as COPD or diabetes, while emphasizing the need for further research into long-term health implications and harm reduction strategies.